Hierarchy concomitant in situ stable iron(II)−carbon source manipulation using ferrocenecarboxylic acid for hydrothermal synthesis of LiFePO4 as high-capacity battery cathode. (1st November 2017) - Yen, Hoxin; Rohan, Rupesh; Chiou, Chun-Yu; Hsieh, Chang-Ju; Bolloju, Satish; Li, Chia-Chen; Yang, Yi-Fei; Ong, Chi-Wi; Lee, Jyh-Tsung
Graphical abstract: Highlights: Fe 3+ Impurities free LiFePO4 has been synthesized via hydrothermal method using ferrocene carboxylic acid as an iron source. Electron paramagnetic resonance spectroscopy has been used for determination of Fe 3+ concentration in LiFePO4 . The LiFePO4 electrode demonstrates good electrochemical performance. Abstract: The iron precursor of lithium iron phosphate (LiFePO4 ) is highly prone to oxidation to Fe 3+ during the hydrothermal synthesis. The Fe 3+ impurities in LiFePO4 restrict the conduction path of Li + ions in LiFePO4, which negatively affect the cell performance. In this paper, we report that ferrocenecarboxylic acid possessing an extremely stable Fe 2+ species and as carbon source has been used successfully to suppress Fe 3+ impurities in LiFePO4 . The X-ray diffraction results reveal that Li2 CO3 first reacts with (NH4 )2 HPO4 to form Li3 PO4 at low temperatures, which above 160 °C further reacts with ferrocenecarboxylic acid to give LiFePO4 . The infrared spectroscopy, nuclear magnetic resonance, mass spectrometry, and elemental analysis results show that the carbon sources during calcination of LiFePO4 are derived from polymers through sequential [4 + 2] cycloaddition reactions of cyclopentadiene and 1, 3-cyclopentadiene-1-carboxylic acid during decomposition of ferrocenecarboxylic acid. The electron paramagnetic resonance results show that the percentage of Fe 3+ in the synthesized LiFePO4 is as low as 0.5 mol%. A plausible reaction mechanism for the hydrothermal synthesis of LiFePO4 is also proposed. The as-synthesized LiFePO4 shows an orthorhombic olivine with a discharge capacity of 158 mAh g −1 at a discharge rate of 0.1C. The cell also shows excellent C-rate and cycle-life performances.